Interaction of the maturation protein of the bacteriophage MS2 and the F pilin of Escherichia coli - Spankie, Timothy J (2020)
Antimicrobial resistance is a ever increasing global concern, with the lack of new antibiotics and misuse of current available antibiotics exacerbating the issue. An alternative approach is to use bacteriophages to infect bacteria and select against the resistant genes, allowing for existing stock to be used again. The maturation protein at the centre of the bacteriophage MS2 infects F plasmid containing bacteria including the entire \acrfull{ecoli}. The maturation protein in the centre of MS2 binds to the F pilus. This project investigates this interaction that delivers the viral DNA into bacteria. The model was ratified and extended through the use of protein-protein docking. A single subunit of the F pilus was compared to a trimer of subunits, and the trimer was found to be a more accurate model, as it included the steric hindrance of other monomer strands when approaching pilin attached to the maturation protein. Contacts between the maturation protein and F pilin were assesed during repeated Molecular Dynamics simulations, where the trimer model was shown to interact less, but within the same regions. Alanine scanning was performed before single-point mutations were made to explore making the maturation protein more versatile to other pili, without reducing the strength of binding to F pilin. After mutations, certain residues were found to be required for the maturation protein and F pilin to interact successfully. Other mutations had no effect on the interaction and some residues had a stronger interaction when mutated than before.